Neonatal Intensive Care Unit Boot Camp: A Preparatory Curriculum for Pediatric Residents - Jeffrey W. Surcouf; Christy G. Mumphrey; Brian M. Barkemeyer; Marlene Buis; Raegan W. Gupta; Staci Olister; Jessica Patrick-Esteve; Dana Rivera; Amy Zeringue; Sheila W. Chauvin (Association of American Medical Colleges, 2018)
Introduction Resident training has changed significantly in recent years, resulting in reduced experiences and practice. Because pediatric residents have fewer required intensive care unit (ICU) rotations, we introduced a neonatal ICU (NICU) boot camp (2014-2015) that continues today to prepare residents immediately prior to beginning an NICU rotation. Methods The NICU boot camp consists of three 1-hour sessions: two interactive lectures with case-based application and one hands-on, integrative learning using simulation. The sessions are designed to cover basic information to assist in daily rounding and decision making while in the NICU. After their NICU rotation, residents complete a 12-item questionnaire. Program evaluation includes direct observation during sessions, faculty debriefing, and a postprogram resident survey. Results Fifty-seven residents participated; questionnaire responses were available from 46 (80.70%). Combined percentages of very useful and extremely useful responses for the three sessions were 82.61%, 78.26%, and 82.60%, with 86.95% for the overall program; 80.40% agreed that repeating boot camp prior to each NICU rotation would be useful. Analysis of narrative responses revealed that participation in boot camp enhanced residents' readiness and confidence for patient care in the NICU and as stated for each educational objective. Discussion Program evaluation results support highly effective and sustainable implementation and achievement of educational objectives. Minor refinements continue for enhancing active learning and content materials and for increasing rigor of program evaluation. Results also suggest that our boot camp may benefit other pediatric programs and serve as a model for use in other resident specialty programs.